Governmentality dan Etika Politik Profetik: Rasionalitas Pemerintahan dalam Kebijakan Publik Indonesia - Zaenal, Wirawan; Razak, Fitriani Sari Handayani; Astuti, Astuti; Amiruddin, Ahmad (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2026)
Contemporary public policy in Indonesia is increasingly shaped by technocratic rationalities operating through performance indicators, audits, and administrative accountability mechanisms. This approach often reduces policy-making to managerial concerns, marginalising its ethical and political dimensions. This article examines governmental rationalities in Indonesian public policy through the lens of governmentality and places them in dialogue with prophetic political ethics. Employing a conceptual–critical approach, the study draws on governmentality literature, prophetic political thought, Indonesian public policy documents, and relevant empirical studies as its analytical basis. The article argues that prophetic politics can be understood as a counter-governmentality to the dominance of technocratic governance. As a form of public political ethics, prophetic politics offers an alternative normative orientation that foregrounds justice, moral responsibility, and human dignity in governing practices. This study contributes to public policy scholarship by integrating power analysis with ethical reflection within the context of Indonesian politics.